The determinants of bank profitability: A cross-country analysis - Tu D. Q. Le; Thanh Ngo (Central Bank Review (CBR), 2020)
This study investigates the determinants of bank profitability in 23 countries from 2002 to 2016 using the system generalized method of moments. The findings indicate that the number of bank cards issued, the number of automated teller machines (ATMs) and the number of point of sale (POS) terminals can improve bank profitability. Hence, this suggests a need for further expansion of these delivery channels. Also, the findings show the negative impact of market power on bank profitability, implying that competition improves bank profitability. Further, the positive relationship between capital market development and bank profitability suggests that they should be considered as complementary to one another.
Keywords: 330; Bank cards; ATMs; POS terminals; Bank profitability; System GMM; Technology